Comparison of Cosyntropin, Vigabatrin, and Combination Therapy in New-Onset Infantile Spasms in a Prospective Randomized Trial. (March 2022) - Knupp, Kelly G.; Coryell, Jason; Singh, Rani K.; Gaillard, William D.; Shellhaas, Renée A.; Koh, Sookyong; Mitchell, Wendy G.; Harini, Chellamani; Millichap, John J.; May, Alison; Dlugos, Dennis; Nickels, Katherine; et al.
Objective: In a randomized trial, we aimed to evaluate the efficacy of cosyntropin injectable suspension, 1 mg/mL, compared to vigabatrin for infantile spasms syndrome. An additional arm was included to assess the efficacy of combination therapy (cosyntropin and vigabatrin) compared with cosyntropin monotherapy.Methods: Children (2 months to 2 years) with new-onset infantile spasms syndrome and hypsarhythmia were randomized into 3 arms: cosyntropin, vigabatrin, and cosyntropin and vigabatrin combined. Daily seizures and adverse events were recorded, and EEG was repeated at day 14 to assess for resolution of hypsarhythmia. The primary outcome measure was the composite of resolution of hypsarhythmia and absence of clinical spasms at day 14. Fisher exact test was used to compare outcomes.Results: 37 children were enrolled and 34 were included in the final efficacy analysis (1 withdrew prior to treatment and 2 did not return seizure diaries). Resolution of both hypsarhythmia and clinical spasms was achieved in in 9 of 12 participants (75%) treated with cosyntropin, 1/9 (11%) vigabatrin, and 5/13 (38%) cosyntropin and vigabatrin combined. The primary comparison of cosyntropin versus vigabatrin was significant (64% [95% confidence interval 21, 82], P  < .01). Adverse events were reported in all 3 treatment arms: 31 (86%) had an adverse event, 7 (19%) had a serious adverse event, and 15 (42%) had an adverse event of special interest with no difference between treatment arms.Significance: This randomized trial was underpowered because of incomplete enrollment, yet it demonstrated that cosyntropin was more effective for short-term outcomes than vigabatrin as initial treatment for infantile spasms.